ISOLASI, KARAKTRISASI DAN PEMURNIAN MINYAK LIMBAH IKAN CAKALANG (Katsuwonus pelamis, L) - Fatimah, Feti (Sainstek, 2010)
Fish represent the ordinary food substance consumed especially for society which live in the coastal area like Town of Manado of Sulawesi Province. This research has conducted to isolate fish oil from cakalang, malalugis, visceral extracted by refluks for 7 hours using chloroform as eluent. Oil quality yielded examined by the acid value and also fatty acid profile determination use the gas chromatography .technique. The purification used the adsorption chromatography by active charcoal.has done to improve the quality of fish oil The result shows that yield of oil obtained from Cakalang fish waste was: 4,67 %, The acid value from Cakalang fish oil was 20,08 %. The EPA and DHA content from cakalang waste oil was 17,96 mg100g oil and 103,08 mg/100g oil There were difference result of fatty acid profile from the purification process. Rate of EPA and DHA was degrade after purified. Keywords: fish oil, cakalang, Manado, adsorption chromatography